Optimising plant form and function for controlled environment agriculture in space and on earth - Muhammad Kamran; Lucas Auroux; Kim Johnson; Mathew G. Lewsey (Modern Agriculture)
Abstract Planned missions to Mars and the moon stress the urgency of developing self‐sustaining food production systems for crewed, long‐term, space exploration. Here we discuss space agriculture (SpaceAg) as a sustainable complete life support system for prolonged space travel and surface missions. The unique challenges and considerations for cultivating crops in space, where radiation, gravity, atmosphere and temperature differ from Earth, are presented. We discuss the selection of suitable crops and approaches to optimise growth traits for the ideal plant form, including the potential of genetic engineering to enhance yield and nutritional content. Plants can serve multiple roles, from providing nutritious foods and wellbeing to acting as biofactories for essential pharmaceuticals. The need for robust and efficient controlled environment agriculture (CEA) systems that are integral to life support is explored. Finally, we discuss promising solutions for sustainable agriculture in controlled environments on Earth, based on SpaceAg research and innovation.